2012
DOI: 10.1016/s1672-2930(12)50023-1
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxic effects of carboplatin in organotypic cultures in chinchillas and rats

Abstract: Carboplatin, a second-generation platinum chemotherapeutic drug, is considerably less ototoxic than cisplatin. While common laboratory species such as mice, guinea pigs and rats are highly resistant to carboplatin ototoxicity, the chinchilla stands out as highly susceptible. Moreover, carboplatin causes an unusual gradient of cell death in chinchillas. Moderate doses selectively damage type I spiral ganglion neurons (SGN) and inner hair cells (IHC) and the lesion tends to be relatively uniform along the length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 114 publications
1
12
0
Order By: Relevance
“…Our results suggest that a peak concentration of cisplatin induces the most severe damage to hair cells, and that hair cells are able to resist damage at higher concentrations which coincides with the reports performed on rats and chinchilla [14,24,25,26]. This unexpected finding may be related to the mechanism of cisplatin resistance, which involves transport of the compound into cells.…”
Section: Discussionsupporting
confidence: 91%
“…Our results suggest that a peak concentration of cisplatin induces the most severe damage to hair cells, and that hair cells are able to resist damage at higher concentrations which coincides with the reports performed on rats and chinchilla [14,24,25,26]. This unexpected finding may be related to the mechanism of cisplatin resistance, which involves transport of the compound into cells.…”
Section: Discussionsupporting
confidence: 91%
“…Our procedures for preparing organotypic cultures from postnatal and adult animals have been described in prior publications (Ding et al, 2012, Ding et al, 2013b, Wei et al, 2010). In brief, animals were euthanized with an overdose of CO 2 , decapitated and the cochleae quickly removed.…”
Section: Methodsmentioning
confidence: 99%
“…Our procedures for preparing and culturing adult whole cochlear explants have been described previously (Ding et al, 2012). In adult rats, the bony cochlea was removed from the temporal bone after decapitation, and perforations were carefully made along the bony surface of cochlear spiral shell in order to permit the flow of culture medium into the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, there are significant differences in carboplatin ototoxicity among different animal species: higher doses of carboplatin damage OHCs in mice, rats and guinea pigs, while in chinchillas it preferentially destroys inner hair cells and type-I spiral ganglion neurons [Ding et al, 1999;Dalian et al, 2012]. However, in clinical studies, carboplatin affects OHCs, as shown by the loss of distortion product otoacoustic emissions (OAEs) [Reavis et al, 2008].…”
mentioning
confidence: 99%